MANAGEMENT OF JOINT PAIN IN THE ELDERLY USING HYPNOTHERAPY IN PANTI SOSIAL TRESNA WERDA BUDI LUHUR JAMBI - Abbasiah, Abbasiah; Handayani, Gusti Lestari; Sovia, Sovia (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2019)
Background: Joint pain is a disease that is much suffered in the elderly, so it is necessary to get attention through pain management treatment. One of the complementary therapies that have been developed and can be an alternative reduction of the use of pharmacological therapy with the management of the unconscious is hypnotherapy. This study aims to determine the influence of hypnotherapy on the joint pain scale in the elderly. Method: This research was a quasi-experiment with one group pre-test-post test design. The study was conducted from August to September 2018, a total of 20 elderly people suffering from joint pain were recruited for the research using purposive sampling method. Data was collected using Verbal Descriptor Scale followed by statistic analisis using the Wilcoxon Signed Ranks Test to compared the average difference in pain before and after the intervention. Results: The results showed no difference in the average pain in the elderly before and after the hypnotherapy intervention (p 0.000 ˂ α 0.05; CI 4.844 – 5.956). Conclusion: Based on the results of the study it can be concluded that there was a hypnotherapy influence on the decrease in joint pain in the elderly.